Analysis Method for Tracer Production Curve in Fractured-vuggy Reservoir. Issue 2 (March 2019) - Shu, Zheng; Zhu, Shijie; Yang, Jie; Zhou, Yuchi; Xu, Haofei; Ye, Zhongbin
Abstract: The fracture-vuggy carbonate reservoir in Tahe oilfield is unique and difficult to be analyzed by conventional tracer analysis technology. Based on the geological characteristics of fracture and vug in reservoirs, a theoretical model is established by applying fluent to simulate the flow characteristics of fluids in fracture-vug, so as to analyze the characteristics of tracers under different conditions: The output of tracer under the condition of single fracture shows kurtosis, while under the condition of single vug without kurtosis; The combination of many fractures can either enhance the peak height or show multiple peaks, while the combination of multiple vugs still shows no kurtosis but only extends the range; The output characteristics of series combination of fracture/vug were more influenced by themselves. The smaller the volume of vug is, the less the fractures were influenced, and thus the production becomes more and more similar to fractures; while the rest of them show vug characteristics. Through applying the tracer production curve analysis theory to the actual production data of the field tracer test, and establishing the fracture tunnel ratio and the dominant channel direction judgement method to characterize the reservoir flow path, we found that the ratio of the fracture and vug in the target area is 1:9; the direction of the dominant channel is determined by the size of the Interdistance intercepting area of the injection production well - the larger the section area is, the better the channel is. It indicates that the analytical method of tracer production curve in fracture-vug reservoir is applicable, and it can lay a foundation for improving the theory of tracer production characteristics analysis in fracture-vug reservoirs.